2021
DOI: 10.51253/pafmj.v71i1.3756
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Medical Students Towards Clinical Relevance of Histology

Abstract: Objective of Study: The objective of this study is to have an insight on student’s attitudes regarding histology’s clinical relevance in public and private sector medical college. Methodology: A cross sectional survey for attitude analysis towards histology’s clinical importance was carried out among 200 third year medical students from private and public sector medical college. Thurdstone and Chave attitude analysis questionnaire was employed to find the attitude score. Results: Students of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The questionnaire was adapted from previous research on the subject. 17–19 , 24–26 A pre-test was conducted on 5% of the sample size to assess the substance and clarity of the questionnaire. During the 2021 academic calendar, all PC-II (Pre-clinical II or second-year medical students), C-I (Clinical year I or third-year medical students), C-II (Clinical year II or fourth-year medical students), and interns undergraduate medical students at Wollo University’s College of Medicine and Health Sciences were participated in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was adapted from previous research on the subject. 17–19 , 24–26 A pre-test was conducted on 5% of the sample size to assess the substance and clarity of the questionnaire. During the 2021 academic calendar, all PC-II (Pre-clinical II or second-year medical students), C-I (Clinical year I or third-year medical students), C-II (Clinical year II or fourth-year medical students), and interns undergraduate medical students at Wollo University’s College of Medicine and Health Sciences were participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…According to a study conducted in Pakistan on the clinical importance of histology, students do not recognize the importance of histology in clinical practice. 17 Another study conducted by Pushpa et al, on the perception and attitudes of first-year medical students in India found that the majority of the students’ attitudes towards histology improved over the course of a year, from ambiguity to clarity, neglect to interest, and lastly, increased self-confidence. 18 Furthermore, medical students have a favorable attitude toward histology, according to a survey done in Serbia on the relevance and attitudes toward histology courses.…”
Section: Introductionmentioning
confidence: 99%
“…24 The current students were of the opinion that, gross anatomy teaching was mostly relevant to the questions asked in various modalities of exams, followed by histology and embryology. Waseem et al 25 reported contradictory results and documented that students ranked histology as less relevant compared to gross anatomy and histology. The students generally think that histology will not help them in their future years.…”
Section: Discussionmentioning
confidence: 99%
“… 5 A study on the clinical importance of histology carried out by Waseem et al showed that students do not realize the significance of histology in their future practice as physicians. 9 In contrast, Pushpa et al, found in a study conducted regarding the attitudes and perceptions of students in their first year of medical education, showed that their attitudes largely improved towards histology after the course of a year, and it changed toward clarity, interest, and self-confidence. 10…”
Section: Introductionmentioning
confidence: 93%